Long term outcome of patients suffering from cancer and Takotsubo syndrome or myocardial infarction - Sattler, Katherine; El-Battrawy, Ibrahim; Gietzen, Thorsten; Lang, Siegfried; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (QJM, 2018)
AbstractBackground. The pathophysiology of takotsubo syndrome (TTS) is unclear so far. There is strong association of the occurrence of TTS and malignant diseas
Gesehen am 02.12.2020